Allelopathic effect of sugar cane straw (Saccharum spp. hybrid) on the arvensis Achyranthes aspera, var. Indica L., under controlled conditions (2022)
Introduction— Allelopathic properties of cane straw are reported, however, information on the effect on some weed species is incomplete. Objective— To evaluate the allelopathic effect of sugarcane straw (Saccharum spp. Hybrid) on germination and initial growth of weed (Achyranthes aspera var. Indica L.) under controlled conditions. Methodology— An experiment was carried out using a completely randomized design with six treatments, including a control and five ratios of straw, 25%, 50%, 75%, 100%, 125%, with four repetitions. The doses used corresponded to the proportion of dry straw biomass/m2 in a cane field. Weed seeds were placed at a depth of 1.0 cm, and germination, dry mass, stem length and radicle length were evaluated. Results— It was evidenced that germination was influenced at 10 days by the different treatments, as well as the dry mass, the length of the stem and the length of the radicle at 7 and 10 days after starting the experiment. Conclusions— The results of the study indicate that the sugarcane straw exerts a negative allelopathic effect on the germination and initial growth of Achyranthes aspera, being the 75% dose the one with the best results.